Estrés académico en la formación online durante la pandemia del COVID-19 en estudiantes de la Facultad de la Educación, el Arte y la Comunicación - Herrera Maza, Joseph Alexander (2022)
In Ecuador, the prevalence of university academic stress have been increasing, currently constituting 83%., The purpose of the study was to identify the sources of academic stress, evaluate the satisfaction of online training and relate both variables, according to sex and age in students of the Faculty of Education, Art and Communication of the National University of Loja, period May-September 2020. Having a quantitative, descriptive, crosssectional approach, with a probabilistic sample of 176 participants between 20-31 years of age; The Academic Stress Inventory and University Student Satisfaction Questionnaire were applied to online training. Getting academic overload was the main source of stress. The second source was the lack of time to carry out academic activities in women between 20- 25 years old and men between 20-31 years old; in women aged 26-31 years, it corresponded to excess responsibility for fulfilling academic obligations. In online training, the aspect with the greatest satisfaction in women aged 20-25 was that related to the teacher-tutor; in women aged 26-31 years and men aged 20-31 years, were those related to the virtual platform. On the other hand, that caused less satisfaction in women between 20 and 25 years old was the one related to communication; in women between 26 - 31 years old and men between 20 - 31 years old they were the general ones of the subject. Concluding that both sexes of 20-25 years old presented a statistically significant relationship between the variables